Characterization of hepatitis B virus genotypes and quantitative hepatitis B surface antigen titres in North American tertiary referral liver centres. (14th June 2013) - Congly, Stephen E.; Wong, Philip; Al‐Busafi, Said A.; Doucette, Karen; Fung, Scott K.; Ghali, Peter; Fonseca, Kevin; Myers, Robert P.; Osiowy, Carla; Coffin, Carla S.
Abstract: Background & Aims: Hepatitis B virus (HBV) genotype and quantitative hepatitis B surface antigen (qHBsAg) have been related to clinical outcome. In this nationwide cross‐sectional study, we aimed to investigate the epidemiology and clinical significance of HBV genotype and qHBsAg in patients with chronic hepatitis B (CHB). Methods: Six hundred and thirty patients with CHB were seen in four urban tertiary referral centres in Canada. HBV genotype was determined by line probe assay (INNO‐LIPA) and HBV DNA quantified by commercial PCR (Roche TaqMan, sensitivity <55 IU/ml or AMPLICOR, sensitivity <60 IU/ml). Titres of qHBsAg were determined by an in‐house assay based on the WHO standard (calibration range 0.24–62.5 IU/ml). Results: In 630 patients (57% male, 69% Asian, median age 42 years), 21% were hepatitis B e antigen positive and the median alanine aminotransferase was 29 U/L. The HBV genotype distribution was A (16%), B (29%), C (31%), D (16%), E (6%). HBV genotype was strongly associated with ethnicity, but neither genotype nor qHBsAg correlated with the degree of fibrosis. In the treatment‐naïve patients, the baseline qHBsAg levels correlated with HBV DNA ( r = 0.2517, P < 0.0008). The median qHBsAg levels were lowest in patients with genotype B ( P < 0.0001), but no significant correlation was noted with all other HBV genotypes. Conclusions: In this large North American HBV epidemiological study, genotypes B and C were the most common; however, all genotypes (A–E) were observed with varied distribution nationwide. Baseline qHBsAg significantly correlated with HBV DNA and with HBV genotype B, but not with liver fibrosis.